Tratamento da anemia e sobrevida de pacientes renais crônicos em hemodiálise - SANTOS, Elton Jonh Freitas (2018)
Anemia is a frequent and inevitable complication of chronic renal disease (CKD) and one of the main risk factors associated with the increase in the morbidity of the CKD. The reduction in the production of erythropoietin is the main reason for the onset of anemia in CKD, as this diagnosis is confirmed, it is recommended the beginning of treatment with an erythropoiesis stimulating agent (ESA). In this context, the aim of the study is to evaluate the level of hemoglobin, the response to treatment with ESA, and the survival of patients on hemodialysis (HD). We performed a prospective, longitudinal analytical study with hemodialysis patients in a reference hospital from May 2015 to April 2017. Clinical, laboratory and data about the drugs used to treat anemia were collected. A longitudinal linear regression model was fitted with random effects to verify the limiting factors of the ESA treatment, and to analyze the factors associated with the patient mortality, was realized a time-dependent Cox models with repeated measures. We enrolled 109 patients (average age, 46.8 (SD ±18.3) years; male, 53.6%. The response to treatment with ESA showed a significant association with age, proportion of urea reduction (PRU), percentage of interdialytic weight gain (%GPDI), body mass index (BMI), use of angiotensin receptor blockers (ARBs), serum iron, and serum albumin. The Variables related to the treatment of anemia that impacted survival were hemoglobin, ESA dose, intravenous iron dose and response to treatment with ESA. However, our findings corroborate that the optimal management of anemia in hemodialysis should be individualized, to identify the limiting factors of treatment and to curb the use of high doses ESA, thus reducing the complications arising from this treatment and the risk of mortality.